2020
DOI: 10.1111/dth.13319
|View full text |Cite
|
Sign up to set email alerts
|

Adapalene gel 0.1% vs ketoconazole cream 2% and their combination in treatment of pityriasis versicolor: A randomized clinical study

Abstract: Pityriasis versicolor (PV) is a chronic superficial fungal infection. Management using azole drugs leads to drug resistance. The present study aimed to compare the clinical outcome of 0.1% adapalene gel vs 2% ketoconazole cream and their combination in PV. This randomized double‐blinded study was conducted on 90 PV patients divided into three equal groups. GI was treated with topical ketoconazole 2% cream twice daily and placebo, GII was treated with topical 0.1% adapalene gel twice daily and placebo and GIII … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 10 publications
0
7
0
1
Order By: Relevance
“…The antiproliferative effect of ADP can be exploited in the treatment of some cancer types [ 22 , 23 , 24 , 25 , 26 ]. In addition to topical combinations of ADP and other active pharmaceutical ingredients (APIs) [ 20 , 27 , 28 ], new therapeutic combinations with orally administered APIs were also reported with good effectiveness [ 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…The antiproliferative effect of ADP can be exploited in the treatment of some cancer types [ 22 , 23 , 24 , 25 , 26 ]. In addition to topical combinations of ADP and other active pharmaceutical ingredients (APIs) [ 20 , 27 , 28 ], new therapeutic combinations with orally administered APIs were also reported with good effectiveness [ 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…166 Studies have shown that combination therapies using 2% ketoconazole cream and 1% adapalene gel are more efficacious in the treatment of tinea versicolor than ketoconazole cream alone. 171,172 To further improve the efficacy of topical ketoconazole, future drug development should focus on improving topical delivery to allow better permeation of drugs into skin by using nanostructured lipid carriers, nanoparticles, microemulsions, copolymeric micelles, niosomes and microemulsions. 156,[173][174][175][176] In this regard, the development of topical gels containing fluconazole-loaded solid lipid nanoparticles allows fluconazole to be used topically as the product exhibits skin penetration as a result of large particle surface area and film formation, enhancing contact between fluconazole and skin.…”
Section: Topical Antifungalsmentioning
confidence: 99%
“…Many other retinoids, including alitretinoin and bexarotene, are effective against mycosis fungoides and Kaposi's sarcoma. Thanks to their RXR-targeting properties (8) .…”
Section: Mechanism Of Actionmentioning
confidence: 99%